Pakistan : Second Review Under the Extended Arrangement and Request for Waivers of Nonobservance of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper assesses Pakistan's Second Review Under the Extended Arrangement and Request for Waivers of Non-Observance of Performance Criteria. Discussions focused on progress in addressing the main macroeconomic challenges facing the country and remedial actions to meet missed performance criteria. Pakistan's economic growth is expected to remain modest with GDP growth forecast revised upward to 3.1 percent. The IMF report highlights that the preliminary data for the first quarter of FY13/14 showed 5 percent growth, mainly driven by services and manufacturing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet